Qaulan Sadidan in QS. An-Nisa Verse 9 and Its Ethical Relevance for Generation Z’s Digital Communication - Ependi, Mahdar; Adenan, Adenan (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study examines the meaning of qaulan sadidan in Q S An Nisa verse 9 and its relevance for the communication practices of Generation Z in contemporary digital environments. While previous research has described the moral significance of qaulan sadidan, few studies have explored how its exegetical interpretations can be connected to current theories of digital communication. This study addresses this gap by combining a thematic reading of classical and modern tafsir with insights drawn from Digital Communication Ethics, Media Ecology, and Self Presentation Theory. Using a qualitative descriptive approach, the analysis engages major exegetical works such as those of al Tabari, Ibn Kathir, al Qurṭubi, Wahbah al Zuhayli, Quraish Shihab, and Zainul Arifin in order to map the development of meaning across interpretive traditions. The findings show that classical exegetes frame qaulan sadidan as upright and fair speech that protects vulnerable individuals and prevents intergenerational injustice, while contemporary exegetes extend its relevance to education, family communication, and public discourse. When viewed in relation to the digital habits of Generation Z, these ethical principles become highly pertinent. They encourage clarity, verification, empathy, and responsibility in navigating rapid information flows, emotionally charged content, and the risks of misinformation and online aggression. The study therefore proposes a Qur’anic ethical communication framework that integrates exegetical insights with contemporary communication theory. This framework contributes to strengthening both Qur’anic literacy and ethical digital literacy among young Muslims and provides a conceptual basis for further research on Islamic communication ethics in the digital age.